La lengua y la glosemática : el disparate histórico (2013)
ABSTRACT: ‘Signifier’ and ‘signified’ are Saussurean terms that encouraged the works of both Jakobson and not-so-popular Louis Hjelmslev. Although Lacan's novel interpretation of Saussure and of Jakobson's ‘phonetics’ influenced his creation of the battery of signifiers, the relevance of Hjelmslev's ‘glossematic theory’ cannot be ignored since Lacan, from the analysis and redefinition of such theory, overcame the conception of language as a sign thanks to his notion of ‘Lalangue’.